Transkulturowe momenty w praktyce tańca flamenco .......... 281 - Romanowska, Jadwiga (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
TRANSCULTURAL MOMENTS IN FLAMENCO DANCE PRACTICEThis text is an introduction to reflection on transcultural moments in dance practice using the example of flamenco. The concept of “transcultural moments” was introduced into the academic discourse by researcher Julie-Anne Boudreau. The term refers to brief intercultural interactions in everyday life that contribute to the formation of our identity and lifestyle. It is the contention of this paper that such transcultural moments also inform the realm of dance. A prime illustration of this phenomenon is flamenco, a dance form that itself emerged from a rich tapestry of transcultural exchange.